Aurora Borealis. Project Cycle Management in Regional Development - Andra Aldea-Partanen; Heimo Keränen; Susanna Nevalainen (European Regional Science Association (ERSA), 2003)
This paper aims to analyse Project Cycle Management approach in the context of regional development. The theoretical framework covers contemporary concepts typical for regional development and specific project/programme management tools. The comparative approach is used to take into account the two versions of Project Cycle Management presented by European Commission among evaluation methods and instruments, in 1993 and 2001. A practical application is drawn using mid-term evaluation of Barents Specialists project, conducted in 2003. Regional development related concepts referred to in this paper include general level concepts such as (but not only) regional development policy, networked environment, learning region, and also specific ones, related to peripherical and Northern regions. In the knowledge era, it is important to consider the role of learning and networking in designing regional development policy in an effective manner. Using standardized tools, as Project Cycle Management might assure the desired efficacy in those cases of projects/programs applying a tailored critical approach of the method. A proper customisation of the tool could be done due to increased awareness and familiarization with Project Cycle Management, after a comparative analysis of the two versions provided by European Commission. Barents Specialists project, a regional development project aiming to explore and develop local skills and knowledge in an innovative way, is used as a practical example. Authors of this paper apply the Project Cycle Management principles to the Barents Specialists project, using the recent mid-term evaluation as starting point. At last, the paper provides recommendations regarding the use of Project Cycle Management in regional development projects/programs.
Keywords: 330